A Comparative Study of the Biodesulfurization Efficiency of Acidithiobacillus ferrooxidans LY01 Cells Domesticated with Ferrous Iron and Pyrite. Issue 6 (2nd July 2016) - Yang, Xinping; Wang, Shimei; Liu, Yujiao; Liang, Yin
ABSTRACT: The high-sulfur coal desulfurization process completed by A. ferrooxidans LY01 cells domesticated with either ferrous iron [Fe(II)] or pyrite (FeS2 ) was investigated in this article. The desulfurization rate for 13 d was as high as 67.8% for the LY01 cells domesticated with pyrite but was only 45.6% for the LY01 cells domesticated with Fe(II). Bacterial adsorption experiments indicated that the bacterial adsorption quantity onto the pyrite particles was similar to the desulfurization efficiency. FTIR analysis showed that chemical composition of the two cell types was similar, but the LY01 cells domesticated with pyrite had higher levels of hydrophobic aromatic R-O groups than cells domesticated with Fe(II). The amount of extracellular polymeric substances (EPS) from the pyrite-domesticated LY01 cells was 1820 μg C/10 10 cells, which was five times more than the amount of EPS in the Fe(II)-domesticated cells; the EPS readily bound Fe(III) with a maximum binding capacity of 0.21 mg Fe(III) per mg C EPS. Strains of pyrite-domesticated LY01 with a high amount of Fe(III) in their EPS possess greater oxidation activity than Fe(II)-domesticated strains with fewer Fe(III). These experiments showed the importance of the substrate-specific differences in the oxidative activity of A. ferrooxidans LY01. In addition, this study provides theoretical guidance for the future optimization of the biodesulfurization process.